The moat house - Stooke, Eleanora H. (Salt Lake City, UT : Project Gutenberg, 2023)
"The Moat House, or 'Sir Jasper's Favourite Niece'" by Eleanora H. Stooke is a novel written in the early 20th century. It centers around the Wallis family, particularly Mrs. Wallis and her two daughters, Celia and Joy, who are invited to stay with Sir Jasper Amery, a wealthy but lonely relative. The story explores themes of social class, family dynamics, and the contrasts between wealth and happiness as the characters navigate their new life at the Moat House. The opening of the book introduces us to the Wallis family, who face financial struggles but maintain a close-knit bond. Joy, the more introspective daughter, is contrasted against her sister Celia, who is eager for the luxurious life the Moat House promises. The family's situation changes when they receive an invitation from Sir Jasper, who wishes to get to know his great-nieces after a long period apart. As they make preparations to leave their modest home for the comforts of the Moat House, they reflect on their current lives and the implications of accepting Sir Jasper's request. This section sets the stage for their new experiences while hinting at underlying tensions regarding wealth and personal values. (This is an automatically generated summary.)
Release date is 2023-03-21
Keywords: Christian life -- Juvenile fiction; Conduct of life -- Juvenile fiction; Faith -- Juvenile fiction; Wealth -- Juvenile fiction; Money -- Juvenile fiction; Happiness -- Juvenile fiction; Contentment -- Juvenile fiction